The Automobile Industry in and Beyond the Crisis - Haugh, David (OECD Economics Department Working Papers, 2010)
This paper considers the role of the automobile industry in the current cycle. It shows that the industry is economically important and its cycle is intertwined with business cycles. After casting some light on the sources of the collapse in car sales at the start of the crisis, the policy measures, in particular car scrapping programmes, put in place to support the automobile industry are discussed. The paper also derives short and medium term projections of car sales. While a rebound in car sales is likely in North America, Japan and the United Kingdom, car sales in Germany have been pushed significantly above trend and may weaken going forward. Over the medium term, in mature markets such as Europe and North America, trend sales are likely to remain stagnant. By contrast, rapid increases are foreseen in China and to a lesser extent in India. Medium-term projections suggest that capacity exceeds trend sales by around 20% in the five largest Western European markets considered as a whole. Without an adjustment in capacity, these countries would need to ensure an ongoing strong export performance. By contrast, automakers in the NAFTA area would need to halt their decline in domestic market share or to rely increasingly on exports in order to avoid excess capacity. In order to maintain their high levels of capacity utilisation, Korean and Japanese manufacturers will need to keep up their strong export performance